2019
DOI: 10.1016/j.bpj.2019.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Biophysics and Structure-Function Relationships of LRRC8-Formed Volume-Regulated Anion Channels

Abstract: Volume-regulated anion channels (VRACs) are key players in regulatory volume decrease of vertebrate cells by mediating the extrusion of chloride and organic osmolytes. They play additional roles in various physiological processes beyond their role in osmotic volume regulation. VRACs are formed by heteromers of LRRC8 proteins; LRRC8A (also called SWELL1) is an essential subunit that combines with any of its paralogs, LRRC8B–E, to form hexameric VRAC complexes. The subunit composition of VRACs determines electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 74 publications
(290 reference statements)
1
35
0
Order By: Relevance
“…Here we present an intra-complex FRET sensor to monitor VRAC activity in live cells with subcellular resolution. The relationship of the observed FRET changes to VRAC gating are clear from numerous common features (Akita and Okada, 2014; König and Stauber, 2019; Pedersen et al, 2016; Strange et al, 2019): (i) the reversible decrease in FRET matches reversible VRAC activation upon treatment with hypo-osmotic solutions, and with the same kinetics as simultaneously-measured whole-cell VRAC currents, (ii) the intensity of the FRET decrease correlates with the applied extracellular hypotonicity; (iii) the modulation of VRAC currents, for example by cholesterol depletion, is mirrored by the observed FRET alteration; (iv) after activation with PMA, FRET rises in hypertonicity as VRAC is inactivated by cell shrinkage. FRET sensors unrelated to VRAC are not affected by hypo-osmotic solutions, demonstrating that the observed changes with our FRET sensor are indeed specific for VRAC activation.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Here we present an intra-complex FRET sensor to monitor VRAC activity in live cells with subcellular resolution. The relationship of the observed FRET changes to VRAC gating are clear from numerous common features (Akita and Okada, 2014; König and Stauber, 2019; Pedersen et al, 2016; Strange et al, 2019): (i) the reversible decrease in FRET matches reversible VRAC activation upon treatment with hypo-osmotic solutions, and with the same kinetics as simultaneously-measured whole-cell VRAC currents, (ii) the intensity of the FRET decrease correlates with the applied extracellular hypotonicity; (iii) the modulation of VRAC currents, for example by cholesterol depletion, is mirrored by the observed FRET alteration; (iv) after activation with PMA, FRET rises in hypertonicity as VRAC is inactivated by cell shrinkage. FRET sensors unrelated to VRAC are not affected by hypo-osmotic solutions, demonstrating that the observed changes with our FRET sensor are indeed specific for VRAC activation.…”
Section: Discussionmentioning
confidence: 96%
“…When cells were treated with the DAG kinase inhibitor DOG, VRAC remained active in isotonic buffer after activation by hypotonicity, even though Γ i recovered to normal levels. The notion that ionic strength directly activates VRACs (Sabirov et al, 2000; Voets et al, 1999) has been controversial (König and Stauber, 2019; Strange et al, 2019). Several studies reported VRAC activation when isotonic fluid was injected into, or inactivation when fluid was withdrawn from the cells without altering the intracellular ionic strength (Best and Brown, 2009; Cannon et al, 1998; Poletto Chaves and Varanda, 2008; Zhang and Lieberman, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Volume regulated anion channel (VRAC) is a ubiquitously expressed chloride channel that has attracted much attention since the molecular structure of VRAC has been identified [4][5][6]. A growing body of evidence indicate that VRAC and their obligatory subunit, LRRC8A have critical roles in many cell functions including cell motility, proliferation, apoptosis, drug and metabolite transport, angiogenesis, and spermatid development, as well as in cell pathophysiological cell functions such as cancer drug resistance, ischemic brain edema, and glaucoma [7][8][9][10][11][12][13][14][15][16][17]. While the molecular structure of VRAC is well documented [18], understanding how VRAC expression at the membrane is regulated has been poorly explored due to lack of appropriate methodology.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, LRRC8C, 8D or 8E was later found to be required together with LRRC8A for functional VSOR activity [51011]. The pore-forming roles of these LRRC8 members were suggested by discernible, though not drastic, alterations of ion selectivity by some point mutations and evidenced by successful reconstitution of anionic channel activity as well as by recent cryo-EM structure studies with purified LRRC8s, as summarized recently [1213]. However, it must be pointed out that several important properties (such as their cytoplasmic ATP independence, smaller single-channel conductance, and little voltage-dependent inactivation kinetics) of LRRC8-reconstituted channels are distinct from those of native VSOR channel, as summarized recently [914].…”
mentioning
confidence: 99%